Analyzing Some Economic and Environmental Returns of Circular Economy in Italy - Zeinab Ali Dashoor (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The present study targets carrying out an analysis of economic and environmental returns as an effect of the adoption of a circular economy in Italy. Some of the key concepts it focuses on are promotion of private circular investment, export of recyclable material, use of circular material, eco-innovation, material footprint, and contribution of renewable energy to the total energy. The present study is supported by the systematic analysis of international data related to the role of circular economy in increasing economic efficiency and reducing environmental costs. The results highlight that private circular investment is highly relevant for the creation of new opportunities for economic development and supporting new, innovative sectors, such as recycling technologies. The results also underlined that eco-innovation plays a crucial role in improving resource efficiency, material footprint reduction, and renewable energy. The study confirms that the circular economy can be a strategic opportunity for Italy to further contribute to renewable energy and to reduce its imported natural resources dependence in a way that is both sustainable and economically competitive. The present study provides valuable insights for decision-makers and policymakers to promote circular economy strategies at national and international levels.